ANALISIS NILAI TAMBAH AKARWANGI PADA INDUSTRI MINYAK ATSIRI DI KABUPATEN MINAHASA UTARA - Grace A Kairupan; Caroline B.D. Pakasi; Celsius Talumingan (Universitas Sam Ratulangi, 2016)
ABSTRACTThis study aims to determine the advantages and value added received by the processing business akarwangi became essential oil.This research has been conducted since December of 2015 until January of 2016 at the X company , located in North Minahasa Regency. Retrieval and data collection included primary data and secondary data. Primary data was obtained from akarwangi crop production effort using questionnaires. Secondary data were obtained from various print and online media as well as from journals and literature relating to this study. Data analysis methods applied in this study, in order to see how the value-added processing of akarwangi into essential oils is the first to use the analysis of business profits and subsequently used analasis value added. The results showed that business processing akarwangi becomes essential oil provides a great advantage, by using the main raw material of akarwangi were harvested from plantation company itself as many as 24. 375 kg can produce 243,75 kg essential oils of akarwangi and the price of essential oil per kilogram is equal Rp. 3,000,000. For the price of akarwangi crops on the market in 2007 approximately Rp. 500 / kg (Indrawanto, 2007) and in 2008 the price reached Rp. 800 / kg (Yuhono 2008), Assuming the price of plant akarwangi rise 6-7% annually then in 2015 the average price of akarwangi plants is Rp. 3000 / kg. Gross revenues derived from the company amounting to Rp. 731 250 000, after deducting expenses totaling Rp. 126.155.000, then the net profit processing business akarwangi in Essential Oils Industry Company X in North Minahasa Regency is Rp. 605.095.000. The biggest cost component is the raw material of Rp. 73.125.000. followed by auxiliary materials costs Rp. 19.750.000. then the depreciation tool cost Rp 16.560.000. and labor costs are determined based on the level of wages that have been agreed, length of work and the number of working days Rp. 12,000,000. as well as a rental fee of Rp. 4,000,000. The lowest cost incurred for cost of electricity is Rp. 720,000. By doing the calculation of value-added analysis, the obtained results of the added value of this business is Rp. 621.905.000 and for the value that is added to the raw material of akarwangi is Rp. 25.514/kg. The amount of added value is derived from the total value added of Rp. 621.905.000 divided by 24. 375 kg amount of raw material akarwangi used and the results is Rp. 25.514/ kg, meaning that for every one kilogram of raw materials akarwangi used can provide additional value of Rp. 25.514. in the production of akarwangi into Essential Oils.